Taxonomic notes and validation of Oenothera acutifolia (Onagraceae) - Woźniak-Chodacka, Monika (Phytotaxa, 2019)
Oenothera Linnaeus (1753: 346) (Onagraceae) is indigenous to North America (Dietrich et al. 1997), where the great diversity of the genus is reflected by its division into 18 sections and several subsections and series (Wagner et al. 2007). At different times and circumstances, particular evening-primrose species have naturalized in other parts of the world—currently they are known from nearly all continents: North and South America, Asia, Australia, Africa and Europe as well (Cleland 1972, Dietrich et al. 1997, Rostański et al. 2004). Reaching new lands, they began to spread and hybridize with each other, which might have resulted in the origin of new species, unknown from the native area (Dietrich et al. 1997).